Precoded iterative OFDM system (2006)
PAPR in OFDM systems is an extensively studied problem that has effects on the power circuitry of emitters and on the maximum power required by them. In this internship report, the PAPR problem is briefly studied along with a pair of techniques that aim to solve it. The first one, signal clipping and filtering, shows a great reduction of PAPR at the expense of system performance. The second one, linear precoding, shows a modest reduction of PAPR while leaving the system performance unchanged over a Gaussian channel. The combination of the two techniques yields a slightly better performance than the one obtained through clipping and filtering alone. Focusing on the receiver, iterative estimation and cancellation of clipping noise is first implemented on a clipped and filtered OFDM signal, yielding promising results over a Gaussian channel. On the Other hand, the performance of a system using an iterative treatment...